Spain : circulars sent out between July 1936 and August 1937 (list) (1937)
018a-0054-001 SPAIN. CIRCULARS SENT OUT BETWEEN JULY 1936 AND AUGUST 1937. Circular No: JULY 27, 1936 N.C.L. Affiliated Unions, Trades Councils, Divisional & Local Labour Parties. APPEAL: HELP THE SPANISH WORKERS. 131 AUGUST 5, 1936 N.C.L. Friends. APPEAL: HELP THE SPANISH WORKERS. 133 AUGUST 10, 1936 T.U.C. Affiliated Unions. APPEAL: HELP FOR SPAIN. 140 AUGUST 18, 1936 N.C.L. Trade Unions, Trades Councils, Constituency & Local Labour Parties. LEAFLET: SPANISH WORKERS' DEFENCE OF DEMOCRACY. - SEPTEMBER 7, 1936 N.C.L. Trade Unions, Constituency Parties, and Literature Secretaries. PAMPHLET: THE DRAMA OF SPAIN, 1931-1936. - JANUARY 1937 L.P. Affiliated Unions, Constituency Parties and Literature Secretaries. PAMPHLET: FASCIST ATROCITIES IN SPAIN. - JANUARY 20, 1937 N.C.L. Certain Affiliated Unions. Statement on the work of the International Solidarity Fond for the Relief of the Workers in Spain. 44 FEBRUARY 3, 1937 L.P. Trade Unions, Literature Secretaries and Constituency Parties (copy sent). LEAFLET: A CATHOLIC LOOKS AT SPAIN - MAY 1937 N.C.L. Affiliated Unions, Trades Councils, Constituency Local Labour Parties, Women's Sections & Leagues of Youth. APPEAL: SAVE THE BASQUE CHILDREN. 292/946/18a/56